A Case-Control Study to Determine the Prognostic Features of Salivary Epithelial Cells in Periodontitis. (October 2016) - Wang, A.; Swinford, C.; Zhao, A.; Ramos, E.D.; Gregory, R.L.; Srinivasan, M.
Periodontitis—a biofilm-induced immunoinflammatory pathology—often progresses gradually, exhibiting periodic bursts and resolution. Exfoliating oral epithelial cells act as reservoirs for key periodontal pathogens, facilitating reinfection or infection of new sites. Since saliva is a rich source of oral epithelial cells, we hypothesized that the microbial and functional profile of salivary epithelial cells (SECs) will reflect the in situ host response and disease severity. We used a case-control study design. Unstimulated whole saliva was collected from 20 chronic periodontitis patients and 20 healthy controls in accordance with the institutional review board. The isolated SECs were assessed for viability by trypan blue exclusion. Gram-stained SECs were analyzed by ImageJ, and Gram stain index (GSI) per SEC was calculated. Equal numbers of SECs from each sample were exposed to 2 periodontal pathogens— Porphyromonas gingivalis and Fusobacterium nucleatum —in biofilm or planktonic formulations at varying proportions. Cytokines in culture supernatants were assessed by ELISA (enzyme-linked immunosorbent assay). Additionally, soluble Toll-like receptor 2 (sTLR-2)—a pattern recognition receptor capable of binding microbial ligands associated with periodontitis—was measured in clarified saliva by ELISA. An increased number of SECs, a higher GSI/SEC, and a lower sTLR-2 were observed in periodontitis saliva as compared with healthy saliva. SECs from periodontitis saliva secreted higher amounts of interleukin 8 in response to P. gingivalis, and the presence of F. nucleatum dampened the response. Nonsurgical periodontal treatment improved clinical parameters, reduced the number of SECs, decreased GSI/SEC, and increased sTLR-2 in clarified saliva. In conclusion, our data suggest that SECs can provide a phenotypically distinct individualized resource for assessing epithelial response to pathogens in the course of periodontal disease. Furthermore, correlation between the sTLR-2 and GSI/SEC suggests that the expression profile of epithelial and soluble Toll-like receptor could provide an indirect measure of periodontal disease–associated dysbiosis. Knowledge Transfer Statement: The results of this study can be used for prognostic evaluation of chronic periodontitis in response to therapy and provide an opportunity for early identification of poor responders. A chip-based simple test incorporating the identified salivary epithelial cell characteristics can be developed and validated for future clinical applications, especially for monitoring patients with increased susceptibility for refractory and/or recurrent periodontitis.